Upgrading the fixed-time artificial insemination (FTAI) protocol in Romanian buffaloes - Ciornei, Stefan Gregore; Roşca, Petru (Frontiers in Veterinary Science, 2023)
The present study describes the challenges of assisted reproduction in Romanian buffaloes while increasing the efficacy of artificial insemination by choosing the most suitable method. The modified fixed-time artificial insemination (FTAI) protocol with sexed semen was used to increase the conception rate. The study included a total of 80 buffalo heifers that received ovarian stimulation (Ovsynch protocol). Two groups (n=40) were randomly selected: a control in which the classic FTAI method was performed, and an experimental group, in which deep intrauterine AI was performed in cows that had developed a dominant follicle (US+UcFTAI). The conception rate (CR) was 63.6% in the experimental group statistically higher (p<0.05) than the control group (30%). The ultrasound examination showed that using, the OvSynch protocol, 82.5% (33/40) of buffaloes developed a dominant follicle (DF) while the distribution between the warm/cold seasons was 75% versus 90%. The CR was 60% during the hot season vs 66,6% during the cold season. At calving, 92.5% female fetuses were born. The improved FTAI method in this study enhanced the results by reducing the waste of sexed semen and maximizing the response to OvSynch, and therefore it can be recommended to practitioners. This study presents preliminary results and highlights that genetic progress is difficult to achieve. A step-by-step approach is needed in order to choose the most suitable biotechnological method for each farm.